The Prevalence of Depression in Older Turkmen Adults in 1389 - Azize Gharanjik; Farahnaz Mohammadi Shahbolaghi; Gholamreza Ansari; Farid Najafi; Shadi Ghaderi; Kazem Ashrafi; Negin Taheri; Robab Sahaf (Sālmand, 2011)
Objectives: The elderly population in the world is growing and, by 2050, it is expected to exceed 20% of the world's population size, with the majority living in developing countries. Psychological disorders are among the most important problems in elderly people. There are some barriers in the elderly with specific race and ethnicity that can lead to difficulty in detection and interpretation of psychological and mood disorders, for instance language and lower education levels. In this survey, the prevalence of depression in elderly Turkmen over 60 years of age was measured based on standard tests.